Modification of the terms of authorisation of the feed additive consisting of canthaxanthin for chickens for fattening, minor poultry species for fattening, laying poultry and poultry reared for laying, ornamental fish and ornamental birds and ornamental breeder hens to include canthaxanthin produced with Yarrowia lipolytica CBS 146148 (DSM Nutritional Products Ltd.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the European Food Safety Authority was asked to deliver a scientific opinion on the proposed modification of the terms of the authorisation of canthaxanthin, regarding the addition of a new production route, by the yeast Yarrowia lipolytica CBS 146148. The additive is already authorised as sensory feed additive for use in feed for chickens for fattening, minor poultry species for fattening, laying poultry, poultry reared for laying, ornamental fish, ornamental birds and ornamental breeder hens. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concludes that canthaxanthin produced with Yarrowia lipolytica CBS 146148 is considered safe for the target species, the consumer and the environment under the current authorised conditions of use. Canthaxanthin is not an irritant to skin or eyes and it is unlikely to be a skin sensitiser. No conclusion can be reached on the respiratory sensitisation of canthaxanthin. In the absence of data, no conclusions on the safety for the user can be reached for any preparation produced with canthaxanthin. Canthaxanthin produced by fermentation with Y. lipolytica CBS 146148 is efficacious as a colouring agent in feed for chickens for fattening and minor poultry species for fattening, laying poultry and poultry reared for laying, ornamental fish and ornamental birds.